PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

High-resolution satellite image fusion using regression kriging - Qingmin Meng; Bruce Borders; Marguerite Madden (International Journal of Remote Sensing, 2010)

Long-Term Effects of Site Preparation Treatments, Complete Competition Control, and Repeated Fertilization on Growth of Slash Pine Plantations in the Flatwoods of the Southeastern United States - Dehai Zhao; Michael Kane; Bruce Borders; Mike Harrison (Forest Science, 2009)
Data through age 26 from a well-designed study established in 1979 were analyzed with a repeated-measures analysis of variance approach to evaluate effects of site preparation treatments, complete competition control, and repeated fertilization on growth of slash pine (Pinus elliottii Engelm.) plantations on Spodosols and non-Spodosols in the flatwoods region of southern Georgia and northern Florida. Complete and sustained vegetation control and repeated fertilization consistently and significantly increased slash pine productivity, with greater responses occurring on Spodosols than on non-Spodosols; their combination had less than additive effects on Spodosols and additive effects on non-Spodosols. Complete and sustained vegetation control resulted in greater cumulative responses than repeated fertilization over more than 20 years, and then the gains from repeated fertilization had caught or surpassed the gains from complete vegetation control. Bedding resulted in significant responses in the early ages. Burning improved stand basal area and volume growth rather than average tree height and dbh on non-Spodosols and had little effect on Spodosols. Chopping had no significant effect on either soil group. Results of this study emphasize the need for site-specific silvicultural prescriptions.

Base–Age Invariant Site Index Models from a Generalized Algebraic Parameter Prediction Approach - Mingliang Wang; Keith Rennolls; Bruce E. Borders (Forest Science, 2008)
A simple idea is proposed to develop polymorphic base–age invariant models with multiple asymptotes: the asymptotic parameter is taken as the site-specific parameter (χ) and one of the other parameters is taken as dependent on χ as a simple power function. This approach is a constrained form of the generalized algebraic difference approach (GADA) and eliminates the requirement in previous GADA models to obtain an explicit solution for χ: χ just has to be estimated along with other parameters of the model. The approach may be used to adapt base–age specific models, developed in terms of the “parameter prediction” method, to be “base–age invariant.” The new approach and the models it produces are evaluated on data sets for Chinese fir, red alder, and birch, with models being fitted using the “dummy variable” method in which each observed data series has its own site-specific χ parameter. The base–age invariant models developed are superior to their comparable base–age specific models.

Problems of Scaling Plantation Plot Diameter Distributions to Stand Level - Bruce E. Borders; Mingliang Wang; Dehai Zhao (Forest Science, 2008)
Diameter distribution models are used extensively in forest growth and yield modeling. They are usually fitted with fixed area sample plot data but applied at the stand level, the unit of forest production planning. In this process, the distribution obtained at the plot level is assumed to be representative of that at the stand level. In other words, the distribution from each plot of the same stand is assumed (roughly) to be the same, and therefore we can reasonably scale the plot distribution to the stand level. However, because of site-induced within-stand (between-plot) variability and spatial correlation introduced by tree competition and/or microsite effects or other factors, plot distributions may differ markedly from the stand distribution. We use data from 11 slash pine (Pinus elliottii) plantations, each consisting of 10 plots, to address differences in diameter distributions between plot level and stand level. The data indicate that (single) plot distributions are generally significantly different from their stand counterparts, because of spatial heterogeneity among plots within a given stand. For relatively homogeneous stands, diameter distributions obtained by averaging two to three plots may well represent the stand distribution within a certain precision, whereas for stands with more obvious spatial heterogeneity, a relatively large number of plots seem to be necessary for characterizing the stand distribution.

Parameter Estimation of Base-Age Invariant Site Index Models: Which Data Structure to Use?—Reply - Mingliang Wang; Bruce E. Borders; Dehai Zhao (Forest Science, 2008)

Parameter Estimation of Base-Age Invariant Site Index Models: Which Data Structure to Use? - Mingliang Wang; Bruce Borders; Dehai Zhao (Forest Science, 2007)
Two main approaches to estimating parameters of dominant height curves (derived by algebraic difference approach (ADA) and generalized ADA (GADA)), the dummy variable method and the difference approach (the error-in-variable (EIV) method along with ordinary least-squares (OLS) fits)are compared using second-rotation loblolly pine (Pinus taeda L.) data from a designed experiment. It was found that the EIV method consistently performed better than the dummy variable method, and the two unbiased estimation methods were not necessarily better than the biased OLS differencemethods. In general, the performance of these two approaches was similar in height prediction given site index, but in combination with site index prediction given heights, the difference methods generally performed better. The nonoverlapping forward difference data structure (III), is recommendedto fit difference models.

A Multilevel Approach to Individual Tree Survival Prediction - Charles E. Rose; Daniel B. Hall; Barry D. Shiver; Michael L. Clutter; Bruce Borders (Forest Science, 2006)
Traditionally, modeling of permanent plot individual tree survival has not considered the multiple sources of heterogeneity and correlation that may arise due to the multilevel data structure inherent in the design (e.g., clustering of trees within a plot). Permanent plots are sampled periodically; therefore, data are interval-censored because it is only known that a tree died between two successive measurement occasions. Here, we adopt the complementary log–log (CLL) function for modeling permanent plot interval-censored individual tree survival data. The CLL function is derived directly from the likelihood function of a fully specified statistical model that accounts for interval censoring. In addition, our CLL model considers silvicultural treatment effects on survival. Our data are from young permanent plot loblolly pine plantations that have been measured annually beginning at age 1 year. Each plot was randomly assigned one of four cultural treatments:control (C), herbicide (H), fertilization (F), and herbicide and fertilization (HF). Here we extend the individual tree survival CLL model to allow for trees within a plot and plot level random effects. We demonstrate individual tree survival predictions with and without the inclusion of random effects.

A Generalized Methodology for Developing Whole-Stand Survival Models - Charles E. Rose; Michael L. Clutter; Barry D. Shiver; Daniel B. Hall; Bruce Borders (Forest Science, 2004)
A large source of variability in yield predictions is due to estimation of future surviving trees per unit area. Previous whole-stand survival modeling efforts have concentrated on modeling the empirical survival curve. Modeling hazard functions, an approach to survival analysis commonly used in fields such as medicine and sociology, can be applicable to plantation survival estimation. We offer a generalized method for deriving whole-stand survival models that are capable of modeling complex underlying hazard functions. We use our knowledge of the empirical hazard function to limit our selection to appropriate functions. Integrating selected functions results in initial condition difference equations that, when fitted to our data, provide biologically reasonable whole-stand survival predictions and adequately represent the underlying hazard function. Our method is relatively easy to implement and can model a whole-stand survival curve with a complex underlying hazard function. FOR. SCI. 50(5):686–695.

A Model for Foliage and Branch Biomass Prediction for Intensively Managed Fast Growing Loblolly Pine - Yujia Zhang; Bruce E. Borders; Rodney E. Will; Hector De Los Santos Posadas (Forest Science, 2004)
Prediction models of foliage and branch biomass were derived based on the foliage distribution within the crown and the pipe model theory. Resulting models were fitted to data collected from intensively managed loblolly pine (Pinus taeda L.) plantations in the Lower Coastal Plain and Piedmont of Georgia. We found that diameter outside bark at the base of the live crown, crown height, and crown length are key predictors of foliage biomass. Together they produce reliable predictions of foliage and branch biomass for stands managed under a wide array of silvicultural treatments. The model indicates that an annual fertilization treatment significantly increased foliage and branch biomass in the Lower Coastal Plain. However, in the Piedmont, complete control of competing vegetation significantly increased foliage and branch biomass. A significant fertilization-age interaction for foliage and branch biomass was also detected in Piedmont stands. FOR. SCI. 50(1):65–80.

Derivation, Fitting, and Implication of a Compatible Stem Taper-Volume-Weight System for Intensively Managed, Fast Growing Loblolly Pine - Yujia Zhang; Bruce E. Borders; Robert L. Bailey (Forest Science, 2002)
Geometry-oriented methodology yielded a compatible taper-volume-weight system of models whose parameters were estimated using data from intensively managed loblolly pine (Pinus taeda L.) plantations in the lower coastal plain of Georgia. Two segments (separated at a stem ratio of 0.60 of total height) depicted taper, volume, and weight variations of the stems as well. The taper function defines stem taper as a proportion of the diameter at breast height. The segmented volume equation was derived from integration of the taper function along the stem, and it can be readily transformed into a ratio volume equation. Likewise, the segmented weight equation was obtained from integration of the volume function and a wood density function. Data analysis showed that fertilization has significantly reduced taper (inside and outside bark) on the upper segment and augmented stem merchantable volume in this segment. However, unit-weight (green wood and bark, green wood only, and dry wood only) was not significantly different between fertilized and unfertilized trees, implying that annual fertilization did not reduce the specific gravity very much. Finally, our analysis showed no significant impacts of complete vegetation control on taper, volume or weight characteristics. FOR. SCI. 48(3):595–607.

Compatible Volume-Taper Models for Loblolly and Slash Pine Based on a System with Segmented-Stem Form Factors - Zixing Fang; Bruce E. Borders; Robert L. Bailey (Forest Science, 2000)
By integrating a variable-form differential equation for taper, a segmented-stem system of models involving a taper equation, merchantable volume equation, and total stem volume equation results. Through the constraints imposed on the coefficients of integration, the taper model is continuous at the inflection points, and all components in the system are compatible with each other. Models are derived for a bole with two inflection points, but the constant form factor model (no inflection point) and one inflection point segmented model can be obtained as special cases by substituting appropriate parameters directly into this more general model. All parameters are shared by the components in this compatible system. Simultaneous parameter estimation techniques are used so that all appropriate information is obtained from the data. Based on stem analysis data for 1,280 loblolly pine (Pinus taeda L.) trees and 871 slash pine (Pinus elliottii Engelm.) trees, improved predictions result with respect to predicting a stem profile when compared to a constant form factor model. For. Sci. 46(1):1-12.